(untitled) (Plant Bulletin, 2024)
Termite monitoring is an important part of designing the management strategy. In the current study, termite activity was observed at four sites in Multan (three structures and one agriculture area). For this purpose, monitoring traps consisted of plastic bin and wood pieces were buried in soil. The termite activity was observed on weekly basis for two months during March and April 2022. The results indicated that there were five species (Odontotermes spp., Microcerotermes spp., Amitermes spp., Microtermes spp. and Coptotermes spp.) infesting the buildings and agriculture area. The lowest termite contacts in traps were observed on the 1st week which were increased with the passage of time (maximum contacts recorded on 4th week of April). Similarly, the numbers of termites were also less at the 1st inspection at all sites (24-2059 numbers per station) and maximum numbers of termites per station were recorded on 4th week of April. The results will be helpful to manage termite infestation.